Mechanisms of the high-temperature internal stress relaxation during creep in alkali-halide single crystals - Matsokin, V.P.; Pakhomova, I.N. (Functional Materials, 2006)
The relaxation process of internal stresses is experimentally investigated at jump-like change of external stresses during creep of NaCl and KCl single crystals. The basic relaxation processes are considered and modeled some of them.
Keywords: creep; internal stresses; dislocations